2021
DOI: 10.3390/healthcare9060761
|View full text |Cite
|
Sign up to set email alerts
|

Wound-Healing and Skin-Moisturizing Effects of Sasa veitchii Extract

Abstract: Sasa veitchii (S. veitchii) is a traditional herb derived from the bamboo genus, which is collectively called Kumazasa. Although Kumazasa extract is believed to have various effects on the skin, there is little scientific evidence for these effects. In this study, we aimed to obtain scientific evidence regarding the wound-healing and skin-moisturizing effects of Kumazasa extract. Kumazasa extract was applied to the skin of a mouse wound model for 14 days, and the wound area and dermal water content were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We have thus far found that various substances cause an increase in AQP3 in the skin and have mentioned their potential as cosmetic materials. [49][50][51][52] In the future, further development of skin aging research is expected by examining the usefulness of these materials using SAMP mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have thus far found that various substances cause an increase in AQP3 in the skin and have mentioned their potential as cosmetic materials. [49][50][51][52] In the future, further development of skin aging research is expected by examining the usefulness of these materials using SAMP mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although we could not clarify the mechanism by which these genes decreased in the SAMP mice, the results suggested that SAMP mice could be a useful tool in skin aging research. We have thus far found that various substances cause an increase in AQP3 in the skin and have mentioned their potential as cosmetic materials 49–52 . In the future, further development of skin aging research is expected by examining the usefulness of these materials using SAMP mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse skin was processed by a previously described method and used for Western blotting 18,19 . Proteins were separated using sodium dodecyl‐sulfate polyacrylamide gel electrophoresis and then transferred to a polyvinylidene difluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse skin was processed by a previously described method and used for Western blotting. 18,19 Proteins were separated using sodium dodecyl-sulfate polyacrylamide gel electrophoresis and then transferred to a polyvinylidene difluoride membrane. The proteins on the membrane were probed with primary (rabbit anti-rat AQP3 antibody, Alomone Labsmouse anti-rabbit glyceraldehyde-3-phosphate | 421 dehydrogenase (GAPDH) antibody, Chemicon International, Inc.) and secondary antibodies (donkey anti-rabbit IgG-HRP antibody, Santa Cruz Biotechnology Inc; donkey anti-mouse IgG-HRP antibody, GE Healthcare).…”
Section: Electrophoresis and Western Blottingmentioning
confidence: 99%
“…It was also found that S. veitchii extract had a proliferative effect on HaCaT cells. 63 Periplaneta americana Periplaneta americana contains polyalcohols, amino acids, pyrimidines, uracils, and proteoglycans (Figure 30). P. americana extract showed effects in wound-healing that depend on the Janus-activated kinase/signal transducer pathway and transcriptional activator 3 (JAK/STAT3) and Smad3 activity.…”
Section: Sasa Veitchiimentioning
confidence: 99%